A Brief Talk on American Cultural Values: Reflected on the Movie the Pursuit of Happiness - Temmy, Temmy (Lingua Cultura, 2009)
America as one of worldâ€™s biggest developed countries has a very strong influence on global economy, politics, education, science, and military. America is also one of teaching Chinese as a foreign language destinations, therefore understanding American cultural values is very important. Article represents American cultural values based on a true story movie "The pursuit of Happiness". Research method applied was library research. It can be concluded that the characters, setting, and conflicts really presented the characteristics of American society.Â Â